Chemical characterization and biological activities of Simmondsia chinensis (Link) C. K. Schneid seeds oil - Baccouch, Noura; Ben Salah, Hichem; Belhadj, Sahla; Hentati, Olfa; Abdennabi, Raed; Gharsallah, Neji; Elfeki, Abdelfattah; Ayedi, Mohamed; Allouche, Noureddine (Cellular and Molecular Biology, 2018)
The chemical composition, main physicochemical properties, and biological activities of Simmondsia chinensis (S. chinensis) seeds oil were studied. The results revealed that the physiochemical characteristics of S. chinensis seeds oil were as follows: acid values 1.15 mg KOH/g, peroxide values 8.00 meq O2 Kg-1, iodine values 80.00 g/100 g of oil and saponification values 92.00 mg KOH/g, phenolic content 50.91 mg gallic acid equivalents/g extract. Gas chromatography analysis indicated that eicosenoic (55.50 %), erucic (20.43 %) and oleic (19.01 %) acids were the most abundant, saturated and unsaturated, fatty acids in the oil. Moreover, the evaluation of their antioxidant (DPPH, TAC), antibacterial, antidiabetic and acetylcholinesterase evinced interesting results. Seeds of S. chinensis constitute a substitute source for stable vegetable oil and protein with regard to nutritional and industrial applications.